The use of the modified micromarsupialization technique in the treatment of bilateral ranula: A clinical case report (Research, Society and Development, 2021)
The phenomena of mucus extraversion results from a (mechanical) trauma of the excretory ducts of a salivary gland, which leads to an accumulation of mucin in the underlying connective tissue of the ducts. These results are classified as mucoceles and ranulas depending on their location. Treatment is surgical, ranging from marsupialization to permanent lesion removal in addition to other decompression techniques. The objective of this article is to report a clinical case in which a bilateral ranula was treated using the modified micromarsupialization technique with a cotton thread suture in size 0. Female patient with 84 years of age presenting leucoderma and hypertension was admitted into the Emergency Room of the Hospital da Restauração Governador Paulo Guerra in Recife, Pernambuco, Brazil, presenting an asymptomatic bilateral volume increase in the oral floor region and mild dysphagia. According to the clinical assessments (anamnesis, general and loco-regional physical examinations) and complementary evaluations, a pathological lesion resulting from the leakage of mucus into the adjacent tissues called a ranula was obtained as a diagnosis  in which it presented a satisfactory clinical response with the micromarsupialization treatment modified with cotton thread suture size 0. The modified micromarsupialization technique for the treatment of a granula showed success and possess the advantage of being a simple procedure reducing operative times. This procedure is also minimally invasive and shows less risk of damage to the surrounding anatomical structures.